2001
DOI: 10.1080/00071660120088470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the mycotoxin aurofusarin on the antioxidant composition and fatty acid profile of quail eggs

Abstract: 1. The effect of the mycotoxin aurofusarin on the antioxidant composition and fatty acid profile of quail eggs was investigated. 2. Thirty eight 45-d-old Japanese quails were divided into two groups (experimental and control, 15 females +4 males in each group) and were fed on a maize-soya diet balanced in all nutrients. The diet of the experimental quails was supplemented with aurofusarin at the level of 26.4 mg/kg feed in the form of Fusarium graminearum culture enriched with aurofusarin. At the beginning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…Several studies have reported that mycotoxins can generate free radicals causing lipid peroxidation and damage to other biological molecules including lipids, proteins and DNA which results in oxidative stress in poultry (Hoehler et al, 1997;Dvorska et al, 2001).Vitamin E is important for its antioxidant functions in the body. To maintain its tissue level adequate supplementation would be necessary during mycotoxicosis.…”
Section: Vitamin E and Mycotoxin Contaminationmentioning
confidence: 99%
“…Several studies have reported that mycotoxins can generate free radicals causing lipid peroxidation and damage to other biological molecules including lipids, proteins and DNA which results in oxidative stress in poultry (Hoehler et al, 1997;Dvorska et al, 2001).Vitamin E is important for its antioxidant functions in the body. To maintain its tissue level adequate supplementation would be necessary during mycotoxicosis.…”
Section: Vitamin E and Mycotoxin Contaminationmentioning
confidence: 99%
“…Aurofusarin is a dimeric naphthoquinone that is toxic to poultry (6,7). Ingestion of this pigment causes significant decreases in the concentrations of vitamins A and E, total carotenoids, lutein, and zeaxanthin in quail egg yolk and increased susceptibility to lipid peroxidation (6). Naturally occurring aurofusarin also has been reported in Fusarium-infected wheat (20).…”
mentioning
confidence: 99%
“…Two pigments produced by G. zeae and F. culmorum, aurofusarin and rubrofusarin, are golden yellow and red, respectively (2,9,38). Aurofusarin is a dimeric naphthoquinone that is toxic to poultry (6,7). Ingestion of this pigment causes significant decreases in the concentrations of vitamins A and E, total carotenoids, lutein, and zeaxanthin in quail egg yolk and increased susceptibility to lipid peroxidation (6).…”
mentioning
confidence: 99%
“…The toxicological effects of aurofusarin and fusarin C have not been studied extensively. Aurofusarin is known to have adverse effects on avian species; it affects the antioxidant composition and the fatty acid profile of the eggs (21). Fusarin C has been shown to have mutagenic properties in the Ames test.…”
mentioning
confidence: 99%